Regioselective N-Functionalization of Tautomerizable Heterocycles through Methyl Trifluoromethanesulfonate-Catalyzed Substitution of Alcohols and Alkyl Group Migrations - Duari, Surajit; Biswas, Subrata; Roy, Arnab; Maity, Srabani; Mishra, Abhishek Kumar; de Souza, Aguinaldo R. [UNESP]; Elsharif, Asma M.; Morgon, Nelson H.; Biswas, Srijit (Wiley, 2022)
A catalytic synthetic strategy has been developed combining two protocols, such as, direct nucleophilic substitution of alcohols followed by X- to N- alkyl group migration (X=O, S) to access N-functionalized benzoxazolones, benzothiazolethiones, indolinone, benzoimidazolethiones, and pyridinones derivatives. Methyl trifluoromethanesulfonate (MeOTf) was found to catalyze the reaction, which revealed the catalytic property of MeOTf. A mechanism was established through experiments as well as DFT calculations wherein the −OH group of alcohols were converted to the corresponding −OMe groups and in situ generated TfOH. The −OMe groups produced underwent TfOH catalyzed −X alkylation (X=O, S) of the heterocycles followed by −X- to −N-alkyl group migrations in a single step. (Figure presented.).
Keywords: Alcohols; Alkylation; Heterocycles; MeOTf Catalyst; Nucleophilic Substitution; Rearrangement